Opioid, antipsychotic and hypnotic use in end of life in long-term care facilities in six European countries: results of PACE. (4th October 2018) - Tanghe, Marc; Van Den Noortgate, Nele; Pivodic, Lara; Deliens, Luc; Onwuteaka-Philipsen, Bregje; Szczerbińska, Katarzyna; Finne-Soveri, Harriet; Collingridge-Moore, Danni; Gambassi, Giovanni; Van den Block, Lieve; Piers, Ruth; ,
Abstract: Background: Opioids, antipsychotics and hypnotics are recommended for comfort care in dying. We studied their prescription during the last 3 days in residents deceased in the long-term care facility (LTCF). Methods: In a retrospective, cross-sectional survey in Belgium, England, Finland, Italy, the Netherlands and Poland, LTCFs, selected by proportional stratified random sampling, reported all deaths over the previous 3 months. The nurse most involved in the residents' care reviewed the chart for opioid, antipsychotic and hypnotic prescription, cause of death and comorbidities. Multivariable logistic regression was performed to adjust for resident characteristics. Results: Response rate was 81.6%. We included 1079 deceased residents in 322 LCTFs. Opioid prescription ranged from 18.5% (95% CI: 13.0–25.8) of residents in Poland to 77.9% (95% CI: 69.5–84.5) in the Netherlands, antipsychotic prescription from 4.8% (95% CI: 2.4–9.1) in Finland to 22.4% (95% CI: 14.7–32.4) in Italy, hypnotic prescription from 7.8% (95% CI: 4.6–12.8) in Finland to 47.9% (95% CI: 38.5–57.3) in the Netherlands. Differences in opioid, antipsychotic and hypnotic prescription between countries remained significant ( P < 0.001) when controlling for age, gender, length of stay, cognitive status, cause of death in multilevel, multivariable analyses. Dying from cancer showed higher odds for receiving opioids (OR 3.51; P < 0.001) and hypnotics (OR 2.10; P = 0.010). Conclusions: Opioid, antipsychotic and hypnotic prescription in the dying phase differed significantly between six European countries. Further research should determine the appropriateness of their prescription and refine guidelines especially for LTCF residents dying of non-cancer diseases.